Characteristics of Se’i (Rotenese Smoke Beef) Treated with Roselle Calyces and Liquid Smoke: A Recent Study - Gemini E. M. Malelak; Arnol. E. Manu; Gusti. A. Y. Lestari; I. Gusti. N. Jelantik (Current Topics in Agricultural Sciences Vol. 2, 2021)
The goals of this study were to determine the effects of Roselle calyces (Hibiscus sabdariffa) (RC), liquid smoke (LS), and a combination of both (RCLS) on taste, pH, total plate count (TPC), and cholesterol content in se’i (Rotenese smoke beef). This experiment would produce se’i with better quality. A completely randomized design (CRD) was used for the experiment, which included six treatments and three replications. The six treatments were as follows: Control (C)= se’i conventional (without treatment), RC1 = roselle calyces 4% (v/w), RC2 = roselle calyces 8% (v/w), LS = liquid smoke (5%) (v/w), RCLS1 = roselle calyces 4% + liquid smoke 5%, RCLS2 = roselle calyces 8% + liquid smoke 5%. Data were analyzed using ANOVA, followed by Duncan multiple range tests (DMRT) to detect differences between means. To detect differences between means, the Kruskal Wallis test was used first, followed by the Mann Whitney test. Treatments reduced the aroma and taste score, TPC numbers, and cholesterol content of se’i (P<0.05) but had no effect on the pH value. It can be concluded that roselle and the combination of roselle + Schleichera oleosa liquid smoke are more effective than Schleichera oleosa liquid smoke in reducing bacterial numbers in se’i. Because both Schleichera oleosa liquid smoke and control contain similar bioactive compounds, they have the same effect on taste and TPC numbers. Adding liquid smoke or roselle reduces cholesterol content but has no effect on the pH of se’i.